Penyuluhan Penyegahan Penyakit Demam Berdarah Dengue (DBD) Dan Tuberculosis (TBC) Di Desa Pangalengan - Indri Yuliafitri (CV. Multi Kreasi Media, 2025)
Dengue fever (DHF) and tuberculosis (TB) are two major health problems in Indonesia that require special attention in prevention efforts. Pangalengan Village, as one of the high-risk areas for the spread of these two diseases, faces challenges in the form of an environment that supports the development of Aedes aegypti mosquitoes, as well as low public awareness of TB prevention and treatment. This outreach program aims to increase community awareness and understanding of dengue and TB prevention through a community-based educational campaign. The methods used in this program include the installation of educational posters in strategic locations, direct counseling to the community, and evaluation of the effectiveness of the campaign in increasing the knowledge of residents. The results of the activities showed an increase in awareness and changes in community behavior in implementing a Clean and Healthy Lifestyle (PHBS). The active participation of residents in the Clean Friday program and the involvement of schools and health centers in health education contributed to the success of this program. However, there are still some challenges such as low initial awareness and limited access to health facilities. Therefore, further efforts are needed in the form of more intensive and sustainable counseling, as well as the use of social media to reach more residents. With the collaboration between the government, academics, and local communities, it is hoped that this program can continue to run and have a long-term impact on dengue and TB prevention efforts in Pangalengan Village.